0409 The Efficacy of Afternoon-Evening Sleep Following Night Shifts on Sleep and Alertness in Nurses with Rotating Shift Work Schedule: Real World Data. (27th May 2020) - Kim, J; Han, S; Kim, S; Duffy, J
Abstract: Introduction: The aim of this study was to investigate the efficacy of changing sleep timing to afternoon-evening following nightshifts in hospital nurses with three rapid rotating shift schedules. Methods: Hospital nurses with three rotating shift schedules were enrolled for a 1-month pre-intervention and a 1-month intervention study. During the Intervention, sleep timing following nightshifts was directed to afternoon-evening sleep for 8h time-in-bed (TIB) after 1 PM, and ad-lib sleep schedule for other shifts. Baseline and follow-up evaluation included sleep schedule, sleep duration, Epworth sleepiness scale (ESS), insomnia severity index (ISI) for each shift, Beck depression inventory (BDI), and Beck anxiety inventory (BAI). Sleep was assessed by sleep diary and actigraphy. Alertness during the night shift was evaluated using the Karolinska sleepiness scale (KSS) in the beginning and at the end of the shift by texts sent to their cell phones. The participants were asked to give feedback and a willingness to continue this intervention. Results: A total of 26 subjects (30.7±8.5years, 25 female) finished the study among 29 nurses who participated in the study. The shift work was 6.5±8.0years. The mean morningness-eveningness scale was 42.1±8.0(31-62). TIB following nightshifts were 379.9±91.2 and 478.4±48.7 min for preintervention and intervention, respectively (p=0.001). Total sleep time (TST) was 328.0±91.0 vs. 361.0±70.4min, respectively following nightshifts (p=0.187, Cohen's d rm = 0.467). BDI, BAI, ESS, and ISI were significantly improved after the intervention. 60.7% and 49% of the participants reported improved alertness, and work efficiency during the nightshift. 17.9% and 42.9% of the participants reported increased sleep duration, and improved sleep quality after nightshift, respectively. Only eight participants were willing to continue the afternoon-evening sleep schedule following night shifts. KSS was not different between pre-intervention and intervention. Conclusion: The afternoon-evening sleep schedule modestly increased total sleep time following nightshift. The overall mood, sleepiness and insomnia scale improved after the intervention although the alertness assessed by KSS failed to show the difference. The individual difference should be considered for applying afternoon-evening sleep for rapid rotating shift schedules. Support: 2018 Research award grants from the Korean sleep research society and NRF-2019R1A2C1090643 funded by the Korean national research foundation